Overview of The Rationality of Medication Use In Covid-19 Patients at The Inpatition Installation of The Bhayangkara Hospital, Palangka Raya - Prillyanisa , Pasca; Alexandra, Francsisca Diana; Hanasia; Frethernety, Agnes; Turnip, Oktaviani Naulita (Barigas: Jurnal Riset Mahasiswa, 2025)
Bhayangkara Palangka Raya Hospital is one of the government's referral hospitals for treating COVID-19 patients. COVID-19 patients need good service and treatment because there is no appropriate drug formulary for treating COVID-19 at Bhayangkara Hospital. Currently, the standard for COVID-19 treatment is based on the third edition of the COVID-19 management guidebook. This research aims to understand the rationale for using COVID-19 drugs in patients treated at the Bhayangkara Palangka Raya Hospital Outpatient Installation.The type of research used is descriptive qualitative. This research uses the method Total Sampling. The samples in this study were patients who received COVID-19 drug therapy and were hospitalized at Bhayangkara Palangka Raya Hospital who met the inclusion criteria for the July-August 2021 period. There are 6 indicators of rationality for drug use, namely correct indication, correct drug, correct dose, correct duration and method. administration, and be aware of side effects. In this study, a sample of 41 patients was taken. Based on the results of research evaluating the rationality of using COVID-19 drugs in the Bhayangkara Hospital Palangka RayaInpatient Installation for the period July-August 2021 based on the COVID-19 management guidebook, 3rd edition of 2020, in terms of 6 indicators of rationality, it was concluded that the analysis results were correct indications (100% ), the right drug (100%), the right patient (100%), the right dose (100%), the right duration and method of administration (100%), and being aware of side effects (100%) are completely rational. Judging from the 6 indicators of rationality including the right indication, the right drug, the right patient, the right dose, the right duration and method of administration, being alert to side effects is declared completely rational